2020
DOI: 10.1111/1759-7714.13424
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations of individualized medical treatment and common adverse events management for lung cancer patients during the outbreak of COVID‐19 epidemic

Abstract: Since its outbreak in December 2019 in China, the novel coronavirus disease has rapidly spread and affected several countries. It has resulted in a difficult situation for cancer patients owing to the risks of the epidemic situation outbreak as well as cancer. Patients with cancer are more likely than the general population to contract COVID-19 because of the systemic immunosuppressive status caused by malignant diseases or anticancer treatment. Lung cancer has the highest morbidity and mortality in China and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
(29 reference statements)
0
20
0
9
Order By: Relevance
“…A retrospective study of 1.524 patients with cancer revealed a higher risk of COVID-19 (odds ratio [OR], 2.31; 95% CI, 1.89-3.02) compared with the community [14]. Another study showed that among patients infected with SARS-CoV-2, those with malignant tumors progress to severe disease more rapidly than noncancer patients (13 vs. 43 days, p < 0.0001) and severe cases were approximately ve times higher in cancer patients than in the general population (39% vs. 8%, p=0.0003) [15]. Williams et al [16] concluded that cancer patients have >5% mortality compared to cancer-free patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study of 1.524 patients with cancer revealed a higher risk of COVID-19 (odds ratio [OR], 2.31; 95% CI, 1.89-3.02) compared with the community [14]. Another study showed that among patients infected with SARS-CoV-2, those with malignant tumors progress to severe disease more rapidly than noncancer patients (13 vs. 43 days, p < 0.0001) and severe cases were approximately ve times higher in cancer patients than in the general population (39% vs. 8%, p=0.0003) [15]. Williams et al [16] concluded that cancer patients have >5% mortality compared to cancer-free patients.…”
Section: Discussionmentioning
confidence: 99%
“…The novel SARS-CoV-2 virus rst appeared at the end of 2019 in China, is now a worldwide problem that has spread rapidly in several other countries in less than two months [1]. On March 11, 2020, COVID-19 was categorized as a pandemic when over 118.000 cases were diagnosed worldwide [2].…”
Section: Introductionmentioning
confidence: 99%
“…Pacientes portadores de neoplasias malignas hematológicas, pessoas em tratamentos que impactem na imunidade, como a quimioterapia, além de recém--operados e portadores de cânceres muito avançados, que apresentem grande debilidade física, fazem parte de uma população especial que apresenta condições vulneráveis relacionadas à possibilidade de infecções virais, incluindo o Sars-CoV-2. Ademais, considerando os pacientes oncológicos em tratamento, a saturação do sistema de saúde, que está com os recursos voltados ao atendimento da pandemia, pode dificultar no tratamento pleno e íntegro da sua doença [19][20][21][22]29,31,34 . Dessa forma, durante esse período de pandemia, a mortalidade desses pacientes pode aumentar em razão da infecção e da não prestação de tratamento adequado ao câncer 30,35,36 .…”
Section: Discussionunclassified
“…O diagnóstico e o tratamento oncológico durante a atual pandemia devem ter como objetivo limitar os riscos causados pela infecção pelo vírus Sars-CoV-2 sem prejudicar a chance de cura de cada paciente, adaptando--se aos melhores recursos disponíveis 23,24,29 . Apesar dessa prerrogativa, sabe-se que, por conta da individualidade de cada tipo de câncer, das características de cada paciente e dos serviços de oncologia, é impossível estabelecer recomendações que possam ser aplicadas a todos de forma automatizada e, assim, cada caso deve ser avaliado individualmente em busca da melhor estratégia 19,21,[24][25][26]32,34 .…”
Section: Discussionunclassified
“…Cancer patients are more likely to develop COVID-19 than the general population due to malignancies-related chronic immunosuppressive and anti-cancer therapy [85,104]. Patients with lung cancer are more susceptible to COVID-19 since they are typically smokers and old patients with eventual occurrence of treatment-related immune deficiency [140][141][142]. Smokers increase their risk of lung disease, including lung cancer, and are likely to be more vulnerable to COVID-19.…”
Section: Key Entry Genes Of Sars-cov-2 and Human Cancers Including Lumentioning
confidence: 99%